Vécu psychopathologique des personnes âgees : syndrome de glissement au centre de gerontologie de Libreville - Jean-Romuald SIBY (Revue Hybrides)
Like Western countries, in Gabon, there is an accommodation center for the elderly. However, in the African societies of yesteryear, the elderly were sacred, cared for and respected. How did we get to this point? This article offers a global reading of normal and pathological aging by showing how in the clinic of the elderly, the social, cultural, somatic and psychological dimensions are articulated and interdependent, as are the singular, family and institutional dimensions. It also lifts a taboo, namely the abandonment of elderly people by families. The study used a clinical method through case study to analyze and interpret the experiences of elderly people in residence at the gerontology center in Gabon. We note that these elderly people have a very difficult time with family abandonment and accommodation in the geriatric gerontology center. This experience of suffering manifests itself in the appearance of a sliding syndrome, a sign of pathological aging. Faced with this alarming observation which poses a vital prognosis for the elderly, we note a mobilization of staff, particularly psychologists, in plural care in order to help residents. This article thus addresses the representations of aging in this new African society: social representations but also self-representations among the elderly through lived experience. It will then make it possible to identify the issues specific to aging in institutions but will also help to better understand the elderly and care for them. Finally, it shows how aging in institutions constitutes a narcissistic castration for the elderly and generates an experience of suffering, a sliding syndrome.